2022
DOI: 10.1021/acsanm.1c02706
|View full text |Cite
|
Sign up to set email alerts
|

Se/Albumin Nanoparticles for Inhibition of Ferroptosis in Tubular Epithelial Cells during Acute Kidney Injury

Abstract: Cisplatin (DDP) is a widely used chemotherapeutic agent that plays an unsubstitutable role in treating various tumors. However, it is crucial to identify solutions and alternatives for DDP-mediated renal injury. This acute kidney injury (AKI) is characterized by the occurrence of ferroptosis, which is defined as an iron-catalyzed regulatory necrosis mediated by excessive lipid peroxidation. To solve this problem, we concentrate on the potential function of nanoparticles to devise a new technique to prevent DDP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Zhou et al recently reported that polydatin enabled to attenuate the cell ferroptosis in cisplatin-induced AKI via regulating system Xc−/GSH/GPX4 pathway and inhibiting iron metabolism disorders ( Zhou et al, 2022 ). Deng et al found Se/Albumin nanoparticles could alleviate cisplatin-induced AKI by inhibiting ferroptosis with a decrease of superoxide dismutase, and up-regulation of GSH and GPX4 ( Deng et al, 2022 ).…”
Section: Ferroptosis Is Involved In the Development Of Akimentioning
confidence: 99%
“…Zhou et al recently reported that polydatin enabled to attenuate the cell ferroptosis in cisplatin-induced AKI via regulating system Xc−/GSH/GPX4 pathway and inhibiting iron metabolism disorders ( Zhou et al, 2022 ). Deng et al found Se/Albumin nanoparticles could alleviate cisplatin-induced AKI by inhibiting ferroptosis with a decrease of superoxide dismutase, and up-regulation of GSH and GPX4 ( Deng et al, 2022 ).…”
Section: Ferroptosis Is Involved In the Development Of Akimentioning
confidence: 99%
“…Among these, selenium, phosphorus, and carbon are essential elements for human physiology [ 183 , 184 ]. Currently, nanoparticles based on these elements have been adopted for AKI treatment, with excellent therapeutic effects and extremely low side effects [ [185] , [186] , [187] , [188] , [189] ]. For example, Rosenkranz et al adopted selenium-doped carbon quantum dots (SeCQDs) for AKI antioxidant therapy ( Fig.…”
Section: Nano-rons-sacrificial Agentsmentioning
confidence: 99%
“…Ferrostatin-1 or polydatin could inhibit ferroptosis in CI-AKI mice by regulating the GSH/GPX4 signaling pathway [114]. In a CI-AKI mouse model, selenium nanoparticle administration effectively inhibited ferroptosis by decreasing lipid peroxide accumulation and increasing GPX4 activity [115]. In addition, Hu et al found that the activation of the vitamin D receptor could inhibit ferroptosis by upregulating GPX4 expression, thereby improving renal function and alleviating kidney injury in CI-AKI mice [116].…”
Section: Acute Kidney Injury (Aki)mentioning
confidence: 99%